Sex differences in the serotonin 1A receptor and serotonin transporter binding in the human brain measured by PET - Jovanovic, Hristina; Lundberg, Johan; Karlsson, Per; Cerin, Åsta; Saijo, Tomoyuki; Varrone, Andrea; Halldin, Christer; Nordström, Anna-Lena (NeuroImage (Orlando, Fla.), 2008)
Women and men differ in serotonin associated psychiatric conditions, such as depression, anxiety and suicide. Despite this, very few studies focus on sex differences in the serotonin system. Of the biomarkers in the serotonin system, serotonin1A (5-HT1A) receptor is implicated in depression, and anxiety and serotonin transporter (5-HTT) is a target for selective serotonin reuptake inhibitors, psychotropic drugs used in the treatment of these disorders. The objective of the present study was to study sex related differences in the 5-HT1A receptor and 5-HTT binding potentials (BPNDs) in healthy humans, in vivo. Positron emission tomography and selective radioligands [11C]WAY100635 and [11C]MADAM were used to evaluate binding potentials for 5-HT1A receptors (14 women and 14 men) and 5-HTT (8 women and 10 men). The binding potentials were estimated both on the level of anatomical regions and voxel wise, derived by the simplified reference tissue model and wavelet/Logan plot parametric image techniques respectively. Compared to men, women had significantly higher 5-HT1A receptor and lower 5-HTT binding potentials in a wide array of cortical and subcortical brain regions. In women, there was a positive correlation between 5-HT1A receptor and 5-HTT binding potentials for the region of hippocampus. Sex differences in 5-HT1A receptor and 5-HTT BPND may reflect biological distinctions in the serotonin system contributing to sex differences in the prevalence of psychiatric disorders such as depression and anxiety. The result of the present study may help in understanding sex differences in drug treatment responses to drugs affecting the serotonin system.